Determinants of Unresponsiveness to Treatment in Cutaneous Leishmaniasis: A Focus on Anthroponotic Form Due to Leishmania tropica - Bamorovat, Mehdi; Sharifi, Iraj; Tavakoli Oliaee, Razieh; Jafarzadeh, Abdollah; Khosravi, Ahmad (Frontiers in Microbiology, 2021)
Cutaneous leishmaniasis (CL) is a curable disease; however, due to various risk factors, unresponsiveness to CL treatments is inevitable. The treatment of CL has been firmly correlated with multiple determinants, such as demographical, clinical and environmental factors, the host’s immune response, poor treatment adherence, the parasite’s genetic make-up and Leishmania RNA virus. This study primarily focuses on the risk factors associated with different therapeutic outcomes following meglumine antimoniate (MA; Glucantime®) treatment and policy approaches to prevent unresponsiveness in CL patients with a focus on anthroponotic form (ACL). Findings suggest that effective preventive and therapeutic measures should be more vigorously implemented, emphasizing endemic areas. Accordingly, extensive training is essential to monitor drug unresponsiveness regularly, especially in tropical regions where the disease is prevalent. Since humans are the fundamental reservoir host of ACL due to L. tropica, prompt detection, early diagnosis, and timely and effective treatment could help control this disease. Furthermore, major challenges and gaps remain: efficacious vaccine, new tools, and expert staff are crucial before CL can be definitively controlled.